2016
DOI: 10.1063/1.4954292
|View full text |Cite
|
Sign up to set email alerts
|

Counter-ion binding and mobility in the presence of hydrophobic polyions – combining molecular dynamics simulations and NMR

Abstract: Counter-ion binding and mobility in aqueous solutions of partially hydrophobic ionene oligoions is studied here by a combination of all-atomic molecular dynamics (MD) , as well as their mixtures; the latter allowing us to probe counter-ion selectivity of these oligoions. We consolidate both structural and dynamic information, in particular simulated radial distribution functions and average residence times of counter-ions in the vicinity of ionenes and NMR data in the form of counter-ion chemical shift and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…It has already been established that different proteins may exhibit distinct ion-specific trends for a given solution property. 13,21 In this section we present a comparison of NMR relaxation measurements for lysozyme (LZM) and BSA proteins. Both of these systems have been studied extensively in the past, lysozyme is overall considered as a more model system.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has already been established that different proteins may exhibit distinct ion-specific trends for a given solution property. 13,21 In this section we present a comparison of NMR relaxation measurements for lysozyme (LZM) and BSA proteins. Both of these systems have been studied extensively in the past, lysozyme is overall considered as a more model system.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies has investigated the consequences of ion binding on the NMR relaxation of ionic nuclei. These include 35 Cl NMR to study the binding of Cl − ions at the surface of metalloenzymes and in competition with metal ions in solution, 4245 but also dealing with charge compensation at a protein surface, 46–49 at a charged micellar surface, 50 or next to a polyelectrolyte chain, 21 which is more closely related to the current scenario. Past studies have shown that ion relaxation is sensitive to the internal motion of the protein 49 and that the quadrupolar coupling constant (QCC) v q = e 2 qQ/h , where e is the elementary charge, Q is the nuclear quadrupole, q the electric field gradient and h the Planck constant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermodynamic and transport properties, such as osmotic coefficients, heats of dilution, transport numbers, and conductivity, show strong dependence on the charge density of the polyelectrolyte’s backbone as well. Interestingly, the spectroscopic methods, such as dielectric relaxation spectroscopy [18, 19], neutron scattering data and NMR [2022], and ultra-fast optical Kerr effect [23], suggest that the ionenes studied, in spite their relatively low backbone charge density (linear charge density parameter ξ varying between 1.44 and 0.67; see Figure 1) show surprisingly hydrophilic character, an exception being 12,12–ionenes with ξ = 0.43 [20]. …”
Section: Introductionmentioning
confidence: 99%